Song of the poison dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2016)
Petra is scared of the hydra dragon she is supposed to bond with, but when the hydra accidentally poisons the King, and the dragon master, Drake, Petra must find a way to connect with her dragon, because only the hydra's song can cure them.